Feasibility of a colon capsule overnight procedure followed by colonoscopy - Brechmann, T.; Schmiegel, W.; Klute, L.; Rösch, T.; Pox, C. (Zeitschrift für Gastroenterologie, 2016)
Background and aim: Due to limited acceptance of colonoscopy as diagnostic and screening test alternatives are warranted. Colon capsule endoscopy (CCE) has been shown to be a possible filter test, but because of logistical issues a second bowel preparation is usually required, if consecutive colonoscopy is needed. We therefore evaluated the feasibility of a single bowel preparation for both overnight CCE and (therapeutical) colonoscopy thereafter.Methods: Patients from two university hospitals referred to undergo colonoscopy were prospectively included in a dual centre feasibility study. A polyethylene glycol (PEG) based bowel preparation-schedule with ingestion of a colon capsule endoscopy (CCE) at 10pm and subsequent colonoscopy at about 12am on the next day was investigated. The first generation PillCam colon capsule was used with 4 different preparation protocols containing several prokinetics in different compositions (i. e. metoclopramide, erythromycin, sennosoides). The main endpoint was the proportion of patients who completed both CCE and colonoscopy; secondary endpoints were capsule transit times, amount of colon seen on CCE, bowel cleanliness, sensitivity and specifity of CCE and patients’ acceptance.Results: 50 patients between 18 and 75 years were included. The sequence of overnight colon capsule endoscopy and colonoscopy was successfully completed in all but one (one refused colonoscopy). The capsule was excreted during recording time in 86 % of examinations, visualization of the complete colon was possible in 60 %, but adequate colon preparation was achieved in only 45 % irrespective of the regimen used. The preparation regimen consisting of a PEG-solution, erythromycin as prokinetic drug followed by PEG-solution as boost showed the largest proportion of adequate preparations. Overall sensitivity and specificity of CCE for polyps of any size were 65 % and 76 %, respectively. 26 of 30 patients (86.7 %) returned the subjective assessment questionnaire. 23 patients (88 %) reported mild to no discomfort or embarrassment during CCE, whereas 15 patients (58 %) did during the preparation procedure. Drinking the purgative solution was the most inconvenient step in 84 % of cases, drinking the boosts during CCE the second inconvenient step (60 %).Conclusion: Overnight CCE-procedure followed by direct capsule-reading is feasible and safe and might avoid repetitive bowel preparation for subsequent colonoscopy. The bowel preparation needs to be improved.
Keywords: kolorektales Adenom; kolorektales Karzinom; gastrointestinale Motilität; Darmkrebsvorsorge; Koloskopie; Videokapselendoskopie des Kolons (VKE); Darmvorbereitung